Modelling the causes and measuring the consequences of cultural tourism: the economic and cultural impacts of cultural tourist attractions - Wang, Jing (2012)
A complete view of cultural tourism requires perspectives on both its economic aspect and its cultural dimension. This thesis presents the first cultural tourist taxonomy in the literature, which classifies the various types of cultural tourists by using fundamental distinctions based on economic theory. It also explains the necessity of classifying cultural tourists into those six well-defined categories, and why it should only be six. Building on McKercher and du Cros (2002), it models the causes and measures the consequences of cultural tourism, and develops a framework for evaluating the economic and cultural impacts caused by cultural tourist attractions. The method of evaluating the economic impact of cultural tourist attractions is based on the causal chain model, and it has improved the approach used in Femandez-Young and Young (2008) and Young et al (2010), which attributes to an attraction the amount of tourist expenditure at the destination caused by the existence of the attraction. The method of measuring the cultural impact is a new contribution to the literature, as this study provides a way to quantify the complex concept of cultural impact, using the ideas of meta-preferences and preference formation (Sen, 1977; 1983; 2002).